Reviewer Acknowledgements: GHMJ (Global Health Management Journal), Volume 8, Number 1, 2025 - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal), 2025)
As GHMJ (Global Health Management Journal) celebrates its 8th anniversary, we take this opportunity to express our deepest gratitude to the dedicated reviewers whose expertise and insights have significantly contributed to the quality and integrity of this edition. This edition of the Global Health Management Journal (Vol. 8, No. 1, 2025) presents a diverse range of research addressing critical health challenges. The editorial underscores the urgency of global health strategies in mitigating the adverse impacts of climate change on human health (Macnab, 2025). A perspective piece examines Thailand’s policies on PM 2.5 air pollution, revealing hidden gaps in environmental health governance (Wongtongtair, 2025). The best practice article highlights the economic and nutritional potential of Crab Abon as a sustainable fishery product in Balikpapan, Indonesia (Haqiqiansyah, et al., 2025). In the research section, studies explore the psychosocial effects of Indonesian soap operas on Malaysian millennials (Perdana, et al., 2025), the role of HIV education in Indonesian schools (Astuti, et al., 2025), and the quality of life in heart failure patients within the obesity paradox framework (Rachmawan, et al, 2025). Other articles analyze personal hygiene among traditional jamu handlers (Suryani, et al., 2025), the transmission risks of tuberculosis in children (Pratiwi, et al., 2025), and the antioxidant and anti-proliferative properties of Murraya koenigii (L.) leaves on breast cancer cells (Nisa, et al., 2025). This collection of articles reflects our ongoing commitment to advancing global health knowledge and solutions. Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/GHMJ.08.01 Each article in this edition has undergone a rigorous double-blind peer review process, ensuring high standards of academic excellence. We extend our heartfelt appreciation to the reviewers who have played a crucial role in refining and enhancing these works. Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Journal Managers Suyitno, M.PHM Maretalinia, M.A  External Reviewers Prof. Dr. Solikhah S.KM., M.Kes. (Universitas Ahmad Dahlan, Indonesia) Dr. Tulus Handra Kadir, M.Pd. (Universitas Negeri Padang, Indonesia) dr. Hawani Sasmaya Prameswari, SpJP. (Universitas Padjajaran, Indonesia) dr. Raymond Pranata (Universitas Pelita Harapan, Indonesia) dr. Tiar Masykuroh Pratamawati, M.M., M.Biomed. (Universitas Swadaya Gunung Jati, Indonesia) Fanisya Dwiyani, S.T, M.Eng. (Sekolah Tinggi Teknologi Cipasung, Indonesia) Fataa Kusumattaqiin, M.Sc. Ph.D (Politeknik Negeri Samarinda, Indonesia) Musparlin Halid, S.Pd., MPH. (Politeknik Medica Farma Husada Mataram) Sari Hastuti, S.SiT., MPH. (Poltekkes Kemenkes Yogyakarta, Indonesia) Siti Rahmah, SKM., MPH. (Poltekes Kemenkes Mamuju, Indonesia) GHMJ (Global Health Management Journal) welcomes scholars and professionals to contribute to the advancement of global health research by joining our team of reviewers. If you are passionate about supporting high-quality publications, we invite you to be part of our review process. Simply register on our website and select the "Reviewer" option during sign-up. Why Join as a Reviewer? Recognition – Your contributions will be acknowledged in each edition you review. Professional Growth – Eligible reviewers may be considered for future roles on our Editorial Board. Exclusive Publishing Opportunity – Enjoy the chance to publish Guest Editorial Papers at no cost.   Acceptance Rate                           : 44% Days to First Editorial Decision : 21 days Days to accept                                : 28 days   Published: 28 February 2025